A linear programming optimization model applied to the decision-making process of a Brazilian e-commerce company - Almeida, Fabrício (2019)
The decision-making process is not always simple and requires a more careful analysis to maximize the company's revenue. This paper proposes a linear programming model applied to the decision-making of the section of quality monitoring and packaging of a Brazilian company of e-commerce, in which the simplex method was used to maximize the company's revenue from historical time data of the activities for each type of product. From the results, it was verified which products should be prioritized, providing a revenue of US$ 74,681.50. In addition, a simulation was applied to include two employees in the process, which would provide a 32.76% increase in the company's profitability and a new revenue of US$ 99,145.00.